Price Volatility and Correlation of Animal Protein Food Commodities in South Sulawesi - Abdul Rahman Nur; Mohammad Natsir; Amruddin; Sri Mardiyati; Muh. Arifin Fattah (Cita konsultindo, 2026)
This study aims to analyze the price fluctuations of beef, broiler chicken, and chicken eggs as sources of animal protein, as well as to analyze the correlation between commodity prices and food inflation in South Sulawesi Province, during 2021–2025. Secondary monthly time series data were obtained from the Strategic Food Price Information Center (PIHPS) and the Central Statistics Agency (BPS). Data were analyzed using coefficient of variation (CV) analysis and Pearson correlation. The results show that beef prices in modern markets fluctuate more (CV 9.16%) than in traditional markets (CV 8.01%), while wholesalers experience the highest volatility in the beef supply chain (CV 11.11%) compared to producers (CV 8.86%) and retailers (CV 8.51%). Broiler chicken prices were more stable in modern markets (CV 12.64%) than in traditional markets (CV 19.82%), but wholesalers again experienced the highest volatility (CV 31.07%), followed by producers (CV 28.56%) and retailers (CV 10.17%). Egg prices were slightly more stable in modern markets than in traditional markets (CV 19.45 vs. 20.24%), while producers recorded the highest volatility (CV 24.06%), followed by wholesalers (CV 21.13%) and retailers (CV 18.54%). Monthly food inflation averaged 0.331% and was highly volatile (CV 5.228%). Pearson correlation analysis revealed a strong and highly significant positive correlation between beef and egg prices (r=0.759; p<0.01), while the correlations between beef and broiler chicken, and between broiler chicken and eggs, were weak and insignificant. The correlation between each animal protein price and food inflation is negative and statistically insignificant, indicating that food inflation in South Sulawesi is mainly driven by other staple commodities.